Plantas e formigas em diferentes usos da terra e técnicas de restauração no Cerrado - Laste, Keila Caroline Dalle [UNESP] (2015)
Among all savannas in the world, the Cerrado (Brazilian savanna) has the largest biodiversity and has been the most threatened by land conversion. The impacts resulting from land use changes on biodiversity have not been assessed and Cerrado restoration is a challenge still to be overcome. We investigated both - plant and ant diversity losses due to land conversion comprising production systems (sugar cane, pasture, short and long cycle forestry) and the success of different restoration techniques (passive or active, the last by planting nursery-raised seedlings of tree species in pure or mixed stands) and two reference ecosystems (cerrado sensu stricto, which is the typical Brazilian savanna, and the Cerradão, which is the forest type savanna resulting from vegetation encroachment after fire suppression). In plots of 5 x 20 m (100 m2), with five replicates per treatment, we evaluated plant density, basal area, height and canopy cover, richness and composition of the plant community, and the taxonomic and functional diversity of ant communities. A total of 247 species were recorded, with huge variation in structural and richness parameters among the vegetation types studied. Planting trees can reach the plant richness and structure of Cerradão, if this is considered the target ecosystem restoration. Richness of this vegetation type, however, are far below that existing in cerrado sensu stricto. Species losses in the typical Brazilian savanna, either due to land conversion or vegetation encroachment are irreversible and cannot be recovered by conventional restoration actions. In total 131 ant species were recorded, with greater richness values in the restoration and reference areas, but a high richness values were also found in different land uses. The ant species composition and the ant functional composition showed differences among treatments, following the complexity of vegetation ...